A surface coating method to modify tracers for positron emission particle tracking (PEPT) measurements of froth flotation - Cole,K; Buffler,A; Cilliers,JJ; Govender,I; Heng,JYY; Liu,C; Parker,DJ; Shah,UV; van,Heerden M; Fan,X (Powder Technology, 2014)
Positron emission particle tracking (PEPT) is a technique by which particle behaviour can be measured in a system of flow. The quality of the measurement is related to the spatial and temporal precision of the PET scanner and the characteristics of the tracer, which must replicate physical and chemical properties of the system bulk. Tracer particles can be made from ion exchange resins which have a high capacity for the commonly used positron emitting radionuclides 18F or 68Ga. However, these resins have a polymer composition and are naturally hydrophilic, which limits their application in systems involving mineral particles. This work presents a method to modify ion exchange resins with a coating to change the physical properties of the tracer. Two types of tracer were fabricated in this way, with hydrophobic and hydrophilic surfaces, to investigate the behaviour of valuable and gangue minerals in froth flotation with PEPT. The PEPT data were used to determine the spatial occupancies of each tracer, showing that the hydrophobic tracer has the highest occupancy in the froth region and the hydrophilic tracer is rarely entrained.